Transperineal Multiparametric Magnetic Resonance Imaging–Ultrasound Fusion Targeted Prostate Biopsy Combined with Standard Template Improves Prostate Cancer Detection. Issue 1 (25th January 2022) - Kim, Michelle M.; Wu, Shulin; Lin, Sharron X.; Crotty, Rory K.; Harisinghani, Mukesh; Feldman, Adam S.; Wu, Chin-Lee; Dahl, Douglas M.
Abstract : Purpose: Transperineal (TP) prostate biopsy provides an effective approach to prostate cancer (PCa) detection. Although transrectal targeted biopsy has been well described, the specific advantage of the standard TP template or TP targeted biopsy using multiparametric (mp) magnetic resonance imaging (MRI)-ultrasound (US) fusion remains less understood and without consensus. Materials and Methods: We identified all men who underwent a transperineal standard 20-core template in addition to a targeted biopsy with mpMRI-US fusion-guided software from September 2019 to February 2021. We assessed and compared clinical, MRI and biopsy characteristics between standard TP template and fusion targeted biopsies. Results: A total of 301 men underwent TP fusion biopsy during the study period. Target lesions on MRI were sampled with 3 targeted cores per patient (IQR 3–4). The overall cancer detection rate was 74.1% and 63.5% by standard template and targeted biopsy, respectively, of which 52.5% and 59.7% were clinically significant (cs) PCa. Combined csPCa detection rate was 62.2%. Of 176 cases with a cancer diagnosis by both biopsy methods, 18.8% were upgraded with targeted biopsies while 18.2% were upgraded with template biopsies. Conclusions: In men with suspicious lesions on mpMRI, TP MRI fusion-guided biopsies combined with standard template provide a higher overall cancer detection rate and higher detection rate of csPCa than the standard template or targeted biopsy alone. In the setting of a suspicious mpMRI prostate lesion, targeted plus standard template should be included as part of the TP biopsy procedure.